GAMIFICATION STRATEGIES IN ARABIC LANGUAGE LEARNING FOR THE PSYCHOLOGICAL RECOVERY OF CHILDREN IN POST-DISASTER AREAS - Intan Afriati (PT. Antis International Publisher, 2026)
Objective: This study explores how gamification strategies can be utilized as an integrative framework to address both psychological recovery and Arabic language learning needs for children in post-disaster areas, who often face post-traumatic mental illness and learning difficulties. Method: A literature review (2020-2025) was conducted to examine the application of gamification aligned with Trauma-Informed Care (TIC) principles. The study highlights how game design elements, such as progression, choice, and collaboration, can address psychological needs for competence, autonomy, and relatedness, especially in post-trauma contexts. Results: The research finds that gamification, when contextualized to local culture and integrated with stress-free, sensitive content, promotes safe and meaningful Arabic language learning. The study also shows that dynamic engagement and positive feedback mechanisms within the game can enhance emotional regulation and resilience, leading to improved Arabic language skills, reduced stress levels, increased motivation, and stronger social bonds. Novelty: This study supports the effectiveness of holistic gamification in language learning as a psycho-educational intervention, providing hope, structure, and empowerment to children affected by disaster.